1987
DOI: 10.1063/1.337886
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Fe single-crystal films grown on (100)GaAs by molecular-beam epitaxy

Abstract: Single-crystal (100)Fe films 90–330 Å thick have been grown on etch-annealed (100)GaAs substrates by molecular-beam-epitaxy techniques. Ferromagnetic resonance data indicate that the two in-plane 〈110〉 directions are inequivalent and, together with magnetometry data, show that the average film magnetization decreases as the thickness decreases. The inequivalence is attributed to the nature of the interface bonding at a (100) zinc-blende surface. The decreased magnetization is attributed to the formation of Fe2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
160
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 376 publications
(173 citation statements)
references
References 13 publications
12
160
0
1
Order By: Relevance
“…Ferromagnetic resonance measurements on thicker films have confirmed that the ͗110͘ aximuths remain inequivalent for films up to 200 Å thick, and that the ͗100͘ azimuths are equivalent easy axes. 4 The corresponding MOKE data for the Fe/GaAs͑001͒-c(4ϫ4) samples are displayed in Fig. 3, and are very similar to those obtained for the 2ϫ4 surface.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Ferromagnetic resonance measurements on thicker films have confirmed that the ͗110͘ aximuths remain inequivalent for films up to 200 Å thick, and that the ͗100͘ azimuths are equivalent easy axes. 4 The corresponding MOKE data for the Fe/GaAs͑001͒-c(4ϫ4) samples are displayed in Fig. 3, and are very similar to those obtained for the 2ϫ4 surface.…”
Section: Resultssupporting
confidence: 59%
“…1 Previous work has shown that high-quality epitaxial growth of ͑bcc͒ Fe can be achieved on GaAs͑110͒ and ͑001͒, due in part to the fact that the bcc Fe lattice constant is approximately half that of zinc-blende GaAs (2a Fe /a GaAs ϭ1.013͒. 2,3 Ex situ magnetic measurements of Fe films greater than 25 Å thick grown on oxide-desorbed GaAs͑001͒ substrates have shown that such films often have an in-plane uniaxial component to the magnetic anisotropy, 4 although an ideal bcc Fe͑001͒ film should have fourfold symmetry. There are a number of mechanisms which may contribute to the evolving magnetic anisotropy of the Fe film, including shape anisotropy, epitaxial strain, step anisotropies, or interfacial compound formation, but the source of the uniaxial component remains an open issue.…”
Section: Introductionmentioning
confidence: 99%
“…The first experimental work focussing solely on magnetism in epitaxial Fe films on GaAs(001) was reported in 1987 by Krebs et al 3 . Their ferromagnetic resonance measurements indicated that whilst the free-energy density for magnetizing the film along the in-plane ⟨100⟩ directions were equivalent, due to the anticipated cubic magnetocrystalline anisotropy in their Fe films, the in-plane ⟨110⟩ directions were inequivalent -indicative of an additional uniaxial magnetic anisotropy term K U with easy-axis oriented along the [110] and hard-axis along the [110] direction.…”
Section: Cubic Anisotropy In a Ferromagnetic Metalmentioning
confidence: 99%
“…5͑a͒ the fourfold magnetocrystalline anisotropy and a superimposed twofold anisotropy with the easy axis at 135°. This uniaxial anisotropy is well known 4,14 and appears whenever Fe is grown on clean GaAs͑001͒ surfaces irrespective of its reconstruction prior to the deposition. 15 It arises from the ͑chemical͒ twofold symmetry of the GaAs͑001͒ surface and is thus a pure interface anisotropy.…”
Section: Variation Of Presputtering Timementioning
confidence: 99%
“…The Fe/ GaAs͑001͒ system has been discussed as a candidate for spin injection right from the beginning 1 and was recently shown to exhibit a spin injection efficiency of 2% at room temperature in epitaxial samples grown by molecular beam epitaxy ͑MBE͒. 3 Pioneering work on the epitaxial growth of Fe on GaAs͑001͒ was performed by Krebs et al 4 in 1987 by extending the MBE technique from semiconductors to metals. The epitaxial growth of this system is not restricted to MBE but can also be achieved by techniques employing sputtering, [5][6][7][8][9][10][11] which is the commonly used thin film deposition method in industry.…”
Section: Introductionmentioning
confidence: 99%